Why Are Some Listeria monocytogenes Genotypes More Likely To Cause Invasive (Brain, Placental) Infection? - José A. Vázquez-Boland (American Society for Microbiology, 2020)
ABSTRACT Although all isolates of the foodborne pathogen Listeria monocytogenes are considered to be pathogenic, epidemiological evidence indicates that certain serovar 4b lineages are more likely to cause severe invasive (neuromeningeal, maternal-fetal) listeriosis. Recently described as L. monocytogenes “hypervirulent” clones, no distinctive bacterial trait has been identified so far that could account for the differential pathogenicity of these strains. Here, we discuss some preliminary observations in experimentally infected mice suggesting that serovar 4b hypervirulent strains may have a hitherto unrecognized capacity for prolonged in vivo survival. We propose the hypothesis that protracted survivability in primary infection foci in liver and spleen—the first target organs after intestinal translocation—may cause L. monocytogenes serovar 4b hypervirulent clones to have a higher probability of secondary dissemination to brain and placenta.